Antimicrobial photodynamic therapy (aPDT) with curcumin and LED, as an enhancement to scaling and root planing in the treatment of residual pockets in diabetic patients: A randomized and controlled split-mouth clinical trial - Ivanaga, Camila Ayumi [UNESP]; Miessi, Daniela Maria Janjacomo [UNESP]; Nuernberg, Marta Aparecida Alberton [UNESP]; Claudio, Marina Módolo [UNESP]; Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP] (Elsevier, 2019)
Introduction: Residual pockets represent a risk factor for periodontal disease progression. Diabetes Mellitus (DM) may impair prognosis after cause-related therapy, mainly due to the chronic hyperglycemia that negatively influences tissue repair. This study evaluated the clinical efficacy of antimicrobial photodynamic therapy (aPDT) with curcumin (CUR) solution (100 mg/L) and LED irradiation (465–485 nm), as an adjunctive therapy to scaling and root planing (SRP), in the treatment of residual pockets in type 2 diabetic patients. Methods: Individuals with type 2 DM and chronic periodontitis presenting at least one residual pocket per quadrant were selected (n = 25). In each patient, all residual pockets with probing depth (PD) ≥5 mm and bleeding on probing (BOP) were allocated to receive, according to quadrant: 1) SRP (SRP group); 2) SRP and irrigation with CUR solution (100 mg/L) (CUR group); 3) SRP and LED irradiation (InGaN, 465–485 nm, 0.78 cm², 78 mW, 100 mW/cm², 60 s) (LED group); 4) SRP, irrigation with CUR solution (100 mg/L), one minute of pre-irradiation, and LED irradiation (InGaN, 465–485 nm, 60 s) (aPDT group). Clinical parameters of PD, gingival recession (GR), clinical attachment level (CAL), BOP and visible plaque index (PI) were evaluated at baseline, three and six months post-therapies. Differences between the examination periods in each group were analyzed by Friedman's test for non-parametric data, while parametric data were submitted to analysis of variance (One-way ANOVA), followed by Tukey's test. Intergroup comparisons were performed by Kruskal-Wallis test. Results: In an intergroup comparison, the mean values for PD, GR, CAL, BOP and PI were not different at baseline, three and six months (p > 0.05). The intragroup comparison evidenced reduction in PD and BOP in all treatment groups at three and six months (p < 0.05). Significant CAL gain was notable only for the aPDT and LED groups at three months in comparison to baseline data (p < 0.05). Conclusion: Treatment of residual pockets in patients with type 2 DM through association of SRP with aPDT (CUR solution 100 mg/L and LED irradiation) or LED irradiation may yield short-term (three months) clinical benefits regarding CAL gain.
Keywords: Antimicrobial photodynamic therapy; Curcumin; Diabetes mellitus; Periodontal debridement; Periodontitis